SONNE cruise SO 152 : TRACERZIRKEL, 28.11.-27.12. 2000, Recife (Brazil) - Pointe a Pitre (Guadeloupe, France) - Rhein, Monika (Institut für Umweltphysik, Universität Bremen, 2001)
The objectives of the hydrographic-, tracer- and current meter measurements during SONNE cruise S-152 are: 1) Spreading of the deep water masses in the western boundary current, 2) Estimate of time scales of spreading from recent ventilated deep water from the Labrador Sea into the tropical Atlantic, 3) Recirculation of the deep water masses in the western tropical Atlantic, 4) Interhemispheric exchange of water masses, 5) Continuation of the tracer measurements along 35°W